Identification and Characterization of Wheat Streak Mosaic Virus Isolates in Wheat-Growing Areas in Brazil - Talita Bernardon Mar; Douglas Lau; Jurema Schons; Paulo Roberto Valle da Silva Pereira; Alan Johnny Carminatti (International Journal of Agronomy)
Wheat streak mosaic virus (WSMV—Potyviridae, Tritimovirus), transmitted by the eriophyid mite Aceria tosichella Keifer (Acari: Eriophyidae), was considered a quarantine pest in South America. Since the first report of virus in Argentina, the vector has been found in Argentina, Uruguay and Brazil. The objective of this work was to determine the occurrence of WSMV in Brazil and characterize isolates from wheat-growing areas. Between 2009 and 2011, a total of 40 samples collected in wheat (Triticum aestivum) growing areas, where the presence of the mite was previously related, were tested by RT-PCR for virus detection. Six isolates of WSMV were obtained and characterized by sequencing. Two of them had their host range determined. The Brazilian WSMV isolates clustered in clade D are closely related to the Argentine isolate Arg2 (FJ348359). As expected, isolates were unable to infect dicotyledons plants. They caused mosaic in Triticum aestivum, Hordeum vulgare, Secale cereale, ×Triticosecale, and Zea mays, and they were also able to infect Avena sativa. The presence of WSMV in wheat-growing areas of the Brazilian state Rio Grande do Sul was confirmed, possibly having been introduced from a common source and/or direct vector bearing virus migration from Argentina.